پاکستان میں تفسیری ادب کا ارتقاء : ایک تجزیاتی مطالعہ: Evolution of Tafsir Qur’an Literature in Pakistan: An Analytical Study - Muhammad Azam; Kashif Mehmood; Hafiz Muhammad Afzal (International Research Journal of Arabic and Islamic Studies, 2024)
The evolution and development of Tafsir Qur'an l literature in Pakistan represent a significant facet of the country's intellectual and religious discourse. This analytical study investigates the factors contributing to the growth and diversification of Tafsir (Quranic exegesis) literature within Pakistan's scholarly landscape. It examines historical contexts, educational institutions, publishing trends, and the influence of prominent scholars in shaping the trajectory of Tafsir studies in the region. The study also delves into contemporary challenges and opportunities faced by Pakistani scholars engaged in Tafsir, considering socio-political contexts and the impact of technological advancements on disseminating Quranic interpretations. Key findings underscore the role of Tafsir in fostering religious literacy, promoting interfaith dialogue, and addressing contemporary issues within the framework of Islamic teachings. This abstract highlights the significance of Pakistan's contributions to global Tafsir scholarship and underscores the ongoing efforts to enrich understanding and application of Quranic principles in the modern era.